2020
DOI: 10.7554/elife.56649
|View full text |Cite
|
Sign up to set email alerts
|

Assigning mitochondrial localization of dual localized proteins using a yeast Bi-Genomic Mitochondrial-Split-GFP

Abstract: A single nuclear gene can be translated into a dual localized protein that distributes between the cytosol and mitochondria. Accumulating evidences show that mitoproteomes contain lots of these dual localized proteins termed echoforms. Unraveling the existence of mitochondrial echoforms using current GFP (Green Fluorescent Protein) fusion microscopy approaches is extremely difficult because the GFP signal of the cytosolic echoform will almost inevitably mask that of the mitochondrial echoform. We there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…A number of recent studies reported alternative approaches to follow the import reaction which resulted in surprising observations: (1) Ribosome profiling revealed that cytosolic chaperones and the signal recognition particle play crucial roles in distinguishing mitochondrial and secretory proteins already at very early steps in their synthesis (Schibich et al, 2016;Doring et al, 2017;Costa et al, 2018); (2) proximity labeling suggested that some mitochondrial proteins, in particular hydrophobic inner membrane proteins, explore the mitochondrial surface already during their synthesis (Jan et al, 2014;Williams et al, 2014; Vardi-Oknin and Arava, 2019; Wang et al, 2019) and that, in vivo, many (if not most) mitochondrial surface proteins are in direct proximity to the ER (Hung et al, 2017;Cho et al, 2020); (3) systematic screens of GFP-tagged protein libraries showed that many mitochondrial proteins are prone to accumulate in non-mitochondrial locations under certain growth conditions, in particular on the ER and within the nucleus (Vitali et al, 2018;Backes et al, 2020;Saladi et al, 2020;Shakya et al, 2020;Xiao et al, 2020) and, maybe even more surprising, observed non-mitochondrial residents in mitochondria (Ruan et al, 2017;Bader et al, 2020); and (4) genetic screens reported a very close cooperation of the mitochondrial and ER surface in protein biogenesis (Kornmann et al, 2009;Papic et al, 2013;Okreglak and Walter, 2014;Gamerdinger et al, 2015;Wohlever et al, 2017;Hansen et al, 2018;Vitali et al, 2018;Dederer et al, 2019;Matsumoto et al, 2019). Thus, in vivo, the surfaces of the ER and of mitochondria apparently vividly cooperate to sort proteins to the correct intracellular location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies reported alternative approaches to follow the import reaction which resulted in surprising observations: (1) Ribosome profiling revealed that cytosolic chaperones and the signal recognition particle play crucial roles in distinguishing mitochondrial and secretory proteins already at very early steps in their synthesis (Schibich et al, 2016;Doring et al, 2017;Costa et al, 2018); (2) proximity labeling suggested that some mitochondrial proteins, in particular hydrophobic inner membrane proteins, explore the mitochondrial surface already during their synthesis (Jan et al, 2014;Williams et al, 2014; Vardi-Oknin and Arava, 2019; Wang et al, 2019) and that, in vivo, many (if not most) mitochondrial surface proteins are in direct proximity to the ER (Hung et al, 2017;Cho et al, 2020); (3) systematic screens of GFP-tagged protein libraries showed that many mitochondrial proteins are prone to accumulate in non-mitochondrial locations under certain growth conditions, in particular on the ER and within the nucleus (Vitali et al, 2018;Backes et al, 2020;Saladi et al, 2020;Shakya et al, 2020;Xiao et al, 2020) and, maybe even more surprising, observed non-mitochondrial residents in mitochondria (Ruan et al, 2017;Bader et al, 2020); and (4) genetic screens reported a very close cooperation of the mitochondrial and ER surface in protein biogenesis (Kornmann et al, 2009;Papic et al, 2013;Okreglak and Walter, 2014;Gamerdinger et al, 2015;Wohlever et al, 2017;Hansen et al, 2018;Vitali et al, 2018;Dederer et al, 2019;Matsumoto et al, 2019). Thus, in vivo, the surfaces of the ER and of mitochondria apparently vividly cooperate to sort proteins to the correct intracellular location.…”
Section: Discussionmentioning
confidence: 99%
“…, 2020 ) and, maybe even more surprising, observed nonmitochondrial residents in mitochondria ( Ruan et al. , 2017 ; Bader et al. , 2020 ); and 4) genetic screens reported a very close cooperation of the mitochondrial and ER surface in protein biogenesis ( Kornmann et al.…”
Section: Discussionmentioning
confidence: 99%
“…This suggest that weak MTS can complement functions in both compartments [ 56 ]. The recently developed BiG-Mito split GFP approach is likely to allow detection of such weak and unexpected MTS sequences, hence expand the list of aaRSs that are dually localized [ 59 ].…”
Section: Protein Import Into Mitochondriamentioning
confidence: 99%
“…Notably, overexpression of the cytosolic variant improved growth under respiratory conditions [58]. Moreover, a Bi-genomic split GFP (BiG-split GFP) system was recently developed, in which the cytosolic aaRS was fused to a GFP fragment, while the rest of GFP was expressed inside the mitochondria; a clear mitochondrial signal was detected when cytosolic HisRS was tested [59]. This further emphasizes a possible role in mitochondria targeting for a weak MTS that is present in the cytosolic variant.…”
Section: Mechanisms Of Dual-localization Of Mt-aarssmentioning
confidence: 99%
See 1 more Smart Citation